Natural Polysaccharides Derived from Fruits and Mushrooms with Anti-inflammatory and Antioxidant Effects - Singh, Taranjit; Kaur, Gagandeep; Singh, Amandeep; Mathur, Harshita; Sandal, Pallavi; Singh, Rajveer; Bhattacharya, Arka (Current Bioactive Compounds, 2024)
A large class of substances known as polysaccharides have a wide range of advantageous therapeutic and nutritional properties. Polysaccharides found in plants and plant components are extracted for the use in treating a number of diseases. Since ancient times, these polysaccharides have been utilized for human wellness. With no or minimal adverse effects, the polysaccharides that were extracted and refined from the fruits exhibit strong antioxidant, antiinflammatory, immunoregulatory, and hepatoprotective action. These fruit polysaccharides are isolated and purified using numerous chromatographic methods. In this review, the polysaccharide obtained from sources such as Rubus chingii, Mulberry, Glycyrrhiza glabra, Lilium davidii, Flammulina velutipes, Angelica sinesis, and Diospyros kaki have been discussed along with their biological activities including DPPH radical scavenging activity, ABTS free radical scavenging assay, Hydroxyl radical scavenging activity and assay for oxygen free radical absorption capacity (ORAC) listed in various studies.
Keywords: fruit